Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.28991/cej-0309132
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength by Incorporating Quarry Dust in Self-Compacting Concrete Grade M35

Abstract: The study has conducted to determine the workability and compressive strength of the self –compacting concrete. The sand has replaced with quarry dust with the proportion of 10, 20, 30 and 40% and super plasticizer was added 0.9%. The experiments were carried out at the Infrastructure University Kuala Lumpur (IUKL) concrete laboratory. Slump flow, J- Ring tests were carried out to determine the workability of self-compacting concrete and compressive strength test was conducted on 7 days and 28th days of curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the hardened state also it is dense, homogeneous, same mechanical properties and durability properties as traditionally vibrated concrete [1]. Mushtaq Ahmad et al [2] has investigated M35 grade concrete as a partial replacement of quarry dust with fine aggregate ranges from 0% to 40% and concluded that 30% replacement have better workability. S.Premkumar et al [3] experimentally investigated the mechanical properties of river sand with a replacement of quarry dust upto 100% and concluded that strength of concrete improves in 100% replacement.…”
Section: Introductionmentioning
confidence: 99%
“…In the hardened state also it is dense, homogeneous, same mechanical properties and durability properties as traditionally vibrated concrete [1]. Mushtaq Ahmad et al [2] has investigated M35 grade concrete as a partial replacement of quarry dust with fine aggregate ranges from 0% to 40% and concluded that 30% replacement have better workability. S.Premkumar et al [3] experimentally investigated the mechanical properties of river sand with a replacement of quarry dust upto 100% and concluded that strength of concrete improves in 100% replacement.…”
Section: Introductionmentioning
confidence: 99%
“…SCC significantly reduces the placement time of concrete in the large section due to easy handling technique. Self-compacting concrete (SCC) may reduce the noise on the worksite caused due to the vibrator use for concrete compacting purpose [1]. In the modern construction demand for concrete material has increased.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fly ash reduces the demand for cement, fine fillers and sand, which are required in high quantities in SCC. Fly Ash has been shown to be an effective addition for SCC providing increased cohesion and reduced sensitivity to changes in water content [1]. The durability of concrete subjected to aggressive environments depends largely on transport properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations